Instructors’ Competence for Enhancing Quality of In-House Training in Maritime Education - Semjonovs, Dmitrijs; Bogdaņecs, Aleksejs; González, Manuel Joaquín Fernández (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Improving instructors’ competence will enhance quality of maritime in-house training (IHT). The research question of this study was: what are the main features of a competent IHT instructor? A mixed-method study using interviews and a questionnaire was conducted among three groups of respondents: 1) safety managers, vetting and technical managers; 2) IHT instructors, and 3) seafarers (including masters, chief engineers, officers and ratings). Professionals of the field were involved in interpretation of results and in elaboration of the recommendations for enhancing quality of IHT.